Can Algorithms Be Trusted? Consumer Trust and Loyalty in AI-Generated Brand Communication - Ács, Sarolta; Szeberényi, András; Deidda, Sara (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study systematically examines how generative artificial intelligence (AI) in brand communication, such as AI-generated social media content, marketing copy, chatbots, and virtual influencers, affects consumer trust and loyalty. Following PRISMA guidelines, a structured literature search was conducted in Scopus and Web of Science. After deduplication and screening, 165 peer-reviewed articles were included in the final analysis. Using thematic categorization, studies were grouped by AI application and trust-related constructs to identify dominant mechanisms and moderators. The findings indicate that AI-mediated communication can both enhance and undermine consumer trust. Competence-based trust is frequently observed in chatbot interactions, whereas generative AI content and AI influencers produce more conditional effects shaped by disclosure, perceived authenticity, anthropomorphism, and cultural context. Despite increased engagement, undisclosed or misaligned AI use may weaken credibility and long-term loyalty. The review highlights conceptual fragmentation and limited longitudinal evidence, proposing a conditional trust formation framework to guide future research on AI-mediated consumer–brand relationships.